Monday

March 30, 2015

March 30, 2015

Posted by **jenna d** on Thursday, January 13, 2011 at 3:14pm.

- math -
**helper**, Thursday, January 13, 2011 at 4:01pmx^2 + 5x + 6 = 0

factors of 6,

2 x 3 = 6

6 x 1 = 6

factors of 6 that add to 5

2 + 3 = 5

6 + 1 = 7

Since, 2 x 3 = 6 AND 2 + 3 = 5

x^2 + 5x +6 = (x + 2)(x + 3)

( x + 2 ) = 0

x = - 2

(x + 3)= 0

x = -3

**Answer this Question**

**Related Questions**

Math - factoring - Solve by factoring: 1.) x^2 - x - 12 = 0

math - 6. Solve by factoring. mē + 8m + 7 = 0 (1 point)8, 7 7, 1 *7, 1 7, 1 7...

Math-Factoring - Hey I need help factoring 5x^4-180x^2. I'm used to factoring ...

math 123 - solve the equation by factoring 3x^2-8x-3=0 (3x+1)(1x-3)=0 Now solve ...

gr 10 math - Solve by factoring. a) x^2 + 3x - 28 = 0 (x+7)(x-4) d)x^2 + 8x + 16...

Math - I cant figure out how to solve this problem Solve by Factoring: 5x^2-32=-...

Math - 2x(x+3) = 0 Is there a way to solve that using the below methods? ...

math - please anwer these: 1) how can i multiply and divide polynomials ...

Math - Solve by factoring x^3-4x^2-3x+18=0

math - Solve by Factoring 2a^2 - 3a = -5